Unplanned 30-day readmissions in orthopaedic trauma - Metcalfe, D; Olufajo, O; Zogg, C; Rios Diaz, A; Harris, M; Weaver, M; Haider, A; Salim, A (Elsevier, 2016)
Introduction: 30-day readmission is increasingly used as a hospital quality metric. The objective of this study was to describe the patient factors associated with unplanned 30-day hospital readmission of orthopaedic trauma patients. Methods: A statewide observational study was undertaken using data from all acute hospitals in California. All hospital inpatients with a primary diagnosis of fracture or dislocation (ICD-9-CM 800-829) were included, except for those with isolated injuries to the skull, face, or ribs. The primary outcome measure was unplanned 30-day readmission to any hospital in California. Results: 416,568 trauma admissions were available for analysis. The overall readmission rate was 6.5%, and 27.3% of readmitted patients presented to a different hospital. Factors significantly associated with readmission were male sex (OR 1.23, 95% CI 1.19-1.27), age 46-65 (2.61 [2.27-2.99]), black race (1.19 [1.11-1.27]), entitlement to publicly funded healthcare (1.38 [1.25-1.52]), Charlson Comorbidity Index ≥2 (1.84 [1.79-1.90]), discharge against medical advice (3.13 [2.67-3.68]), and spinal fracture (1.42 [1.34-1.49]). Major reasons for readmission included: cardiopulmonary disease (25.6%), infections (20.1%), musculoskeletal problems (18.1%), and procedural complications (12.0%). Conclusions: Many orthopaedic trauma readmissions are potentially unrelated to the initial hospitalization. Penalties for unplanned readmissions risk penalizing hospitals that serve disadvantaged communities and treat a high proportion of trauma patients.